Foreign direct investment on economic growth in Nepal: A sector specific analysis - Aryal, Bishnu Raj; Oli, Sudan Kumar; Shah, Gajendra Prasad; Gopali, Sabina (Asian Journal of Empirical Research, 2024)
This paper investigates the impact of Foreign Direct Investment (FDI) on the economic development of Nepal through a comprehensive and sector-specific analysis. With a growing interest in attracting foreign investments to foster economic growth, this study aims to provide nuanced insights into the diverse effects of FDI across various sectors in the context of Nepal. Utilizing a robust methodology that incorporates quantitative and qualitative approaches, the research examines key economic indicators and sectoral performance data over a specified period. This paper employs a sophisticated econometric framework that includes unit root tests to assess the stationarity properties of the time series data, ensuring the reliability of subsequent econometric models. The ECM and ARDL models facilitate the examination of both short-term and long-term dynamics between FDI and economic development variables, ARDL Bound test, is applied to investigate the existence of cointegration among the variables, providing insights into the long-term equilibrium relationship. Additionally, Granger causality tests are conducted to discern the directionality of causal relationships, helping to discern whether FDI leads to economic development or vice versa. The empirical results reveal compelling insights into the relationship between FDI and economic development in Nepal. Robustness checks further validate the reliability of the findings, enhancing the overall robustness and credibility of the study’s empirical results. The comprehensive analysis provides valuable insights for policymakers and stakeholders aiming to formulate targeted strategies for fostering sustainable economic development in Nepal through FDI.